2019
DOI: 10.1111/gcbb.12624
|View full text |Cite
|
Sign up to set email alerts
|

Measured and modelled effect of land‐use change from temperate grassland to Miscanthus on soil carbon stocks after 12 years

Abstract: Soil organic carbon (SOC) is an important carbon pool susceptible to land‐use change (LUC). There are concerns that converting grasslands into the C4 bioenergy crop Miscanthus (to meet demands for renewable energy) could negatively impact SOC, resulting in reductions of greenhouse gas mitigation benefits gained from using Miscanthus as a fuel. This work addresses these concerns by sampling soils (0–30 cm) from a site 12 years (T12) after conversion from marginal agricultural grassland into Miscanthus x gigante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 61 publications
2
11
0
Order By: Relevance
“…), Milner et al () suggest that if the UK land without constraints were planted with miscanthus, 99.6% would see net gains in SOC between 1.5 and 2.5 Mg C ha −1 year −1 . Given that the only substantial negative SOC changes in Figure are located on uplands of high C soils, our simulation for 2010–2019 agrees with this finding, although we caution that the potential for soil C storage under miscanthus largely depends on the land use system it is replacing (Dondini et al, ; Holden et al, ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…), Milner et al () suggest that if the UK land without constraints were planted with miscanthus, 99.6% would see net gains in SOC between 1.5 and 2.5 Mg C ha −1 year −1 . Given that the only substantial negative SOC changes in Figure are located on uplands of high C soils, our simulation for 2010–2019 agrees with this finding, although we caution that the potential for soil C storage under miscanthus largely depends on the land use system it is replacing (Dondini et al, ; Holden et al, ).…”
Section: Discussionsupporting
confidence: 72%
“…We caution that our simulations are for a mature miscanthus crop, and do not include emissions resulting from past land use conversion. Holder et al () modelled miscanthus, underpinned by experimental soil C change, and concluded that C change is dependent on former land use. Converting grassland to miscanthus can increase global warming potential during the first 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…The net release of three primary greenhouse gases (N 2 O, CH 4 , and CO 2 ) is estimated to reduce to an extent of 4.08 t CO 2 ‐eq per hectare per year (Mi et al., 2018). If we divert to grow Miscanthus on the grassland, soil carbon sequestration would be of significant difference in the long run (Holder et al., 2019). In one life cycle (15 years), it is estimated that Miscanthus will release twice amount of greenhouse gas compared to the current habituated grasses.…”
Section: Environmental Impactmentioning
confidence: 99%
“…In most European countries, fossil fuels (coal and gas) are still the main source of energy production and represent a major source of greenhouse gases and air pollution [1,2]. To combat the resulting negative environmental and health impacts, EU members modi-fied their targets for 2030 to achieve at least 40% reduction of greenhouse gases (GHGs) emissions and reach a share of at least 32% in renewable energy compared with 1990 [3].…”
Section: Introductionmentioning
confidence: 99%
“…These lignocellulosic rich feedstocks are mainly perennial grasses such as Miscanthus x giganteus or switchgrass [12,13]. Having in mind the limited area of agricultural land and to avoid the food production conflict, cultivation of such high biomass crops is becoming more favorable on marginal and less fertile lands unsuitable for arable crops [1,11,14]. Hence, the increase in their volume over the past 15 years is justifiable [15].…”
Section: Introductionmentioning
confidence: 99%